Phase angle as an assessment tool in the context of chronic musculoskeletal pain and ion cyclotron resonance treatments: A pilot observational study - Barassi, Giovanni; Panunzio, Maurizio; Prosperi, Loris; Gallenga, Pier Enrico; Guglielmi, Vito; Spaggiari, Piergiorgio; Pellegrino, Raffaello; Iorio, Angelo Di (Edelweiss Applied Science and Technology, 2025)
The assessment of Chronic Musculoskeletal Pain (CMP) is fundamental for its management. An evaluation parameter that is gaining consensus in clinical practice is the Phase Angle (PA), obtained through bioelectrical monitoring with body Bioimpedance Analysis (BIA). To evaluate the reliability of the PA for CMP assessment, data from 53 patients (mean age 60 years) were observed. They had been evaluated through the Numeric Pain Rating Scale (NPRS) and the BIA, before (T0) and after (T1) a cycle of 10 treatment sessions with Ion Cyclotron Resonance (ICR). Following ICR applications, we detected a significant reduction in NPRS and a positive but not significant increase in PA values. Furthermore, given the misalignment in the significance of the positive trend of the two observed variables, it was not possible to define a clear correlation between pain and the bioelectrical values of patients. The study confirms the efficacy of ICR as a therapy for CMP. However, it was not possible to define a clear role of PA as a specific diagnostic tool for CMP. Although PA showed a promising trend, its non-significant correlation to the pain trend suggests investigating the topic in a more thorough and rigorous manner.